Boost Your Vocab! Pelatihan Penguasaan Kosakata Bahasa Inggris me-lalui Aplikasi Interaktif dan AI - Laksmita Rachmawati, Dwita (Innovative Journal of Community Engagement, 2025)
This community service activity aimed to improve elementary school students’ mastery of English vocabulary through training based on interactive applications and artificial intelligence (AI) technology. The program was carried out at SD Negeri Segoropuro, Pasuruan Regency, targeting fifth- and sixth-grade students. The training methods included the delivery of vocabulary materials, hands-on practice using learning applications, and evaluation through pre-tests and post-tests. The results showed a significant increase in post-test scores compared to pre-test scores, indicating that a technology-based approach is effective in enhancing vocabulary mastery. In addition, students demonstrated high enthusiasm in using interactive learning media. This activity highlights that the use of technology can be a strategic alternative in English language learning at the elementary level. Recommendations are directed to schools, teachers, and community service practitioners to adopt similar approaches in efforts to improve the quality of primary education.